The busy brain cure : the eight-week plan to find focus, tame anxiety, and sleep again - Mushtaq, Romie (Hanover Square Press, 2024)
Traditional medicine treats anxiety, adult-onset ADHD, and insomnia as separate diseases. The results are an addictive cycle that Dr. Romie Mushtaq defines as the Busy Brain, using stimulants like caffeine to stay focused and energized during the day, and then using sedatives like alcohol or sleeping pills at night. Based on over twenty years of clinical research, The Busy Brain Cure helps to break the addiction of the stimulant-sedative cycle and restore sleep, sanity, and a sense of connection. --